Systematics of the Neotropical genus Loxozus (Diptera: Neriidae), with notes on distribution and sexual dimorphism - Tatiana A. Sepúlveda; Claudio J. B. de Carvalho; Alessandre Pereira-Colavite (Zoologia (Curitiba), 2019)
The monotypic genus Loxozus Enderlein, 1922 is redescribed. After examining the holotypes of Tetanocera cornuta Walker, 1853 and Loxozus clavicornis Enderlein, 1922, we confirm that these species are synonyms and reiterate that the correct name of the nominal species is Loxozus cornutus (Walker, 1853). The male of L. cornutus is described for the first time and notes on the species’ sexual dimorphism and illustrations of the genitalia are provided, together with distribution data, including new records for Venezuela, Brazil and Peru.